The effectiveness of short-term strategic family therapy on married conflicts - Darbani, Seyed Ali; Farokhzad , Pegah; Lotfi Kashani , Farah (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The aim of this study was to determine the effectiveness of short-term strategic family therapy on marital conflicts. Method: The present study was a semi-experimental one with experimental, control and pre- Test and follow up were two months. The statistical population of this research includes couples who come to the consulting center of oil and gas engineering company, 45 of whom were referred to this center due to marital and familial problems. After matching the subjects, the inclusion and exit criteria of the study were purposefully selected by 20 couples and randomly assigned to experimental and control groups. In this study, 10 couples (20 people) were in the experimental group and 10 couples (20 people) were in the control group. The experimental group received 90 minutes of treatment after 8 pre-tests; but the control group did not receive any treatment after the pre-test. Both groups were evaluated in three stages of pre-test, post-test and 2-month follow-up by the mentioned questionnaires. Repeated measurement analysis of variance test was used to analyze the data. Results: The results showed that short-term strategic family therapy had an effect on improving the conflicts of couples participating in post-test and follow-up (F= 5.92, P= 0.005). Conclusion: Based on the findings, it can be concluded that short-term strategic family therapy, in addition to improving the level of couple adjustment, has also led to a reduction in conflict.